(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
In this article will be study role of ethical criteria in the formulation of the criminal legislative policy in related to the cyberspace. The accountable legislature solicitude; application users of data exchange in the virtual space; is existence on the bed exchange of information and refinement of the scope unnormal. The impurity easily of virtual space to different kinds of contents, auditory, visual and written vulgar or obscene in global scale from one side and the access of users to fast and easy extralimital on the other side, has caused variety of canon and preventive policies to act. Appealing to the criminal sanctions is one of these policies for deleting contents contrary to sacrosanctity and immorality in the virtual space. Production, distribution, publishing, sending, transaction, maintenance and storage immoral or contents of chastity obscene including are remaking behaviors in cyber space. Legislator approved a computer crimes act, a new policy foundation to the natural persons or legal persons perpetrator that crime or access to others contents unethical to facilitate they are guilty.